Design and validation of nurses’ knowledge, attitude and practice questionnaire for discharge planning of stroke patients - Fu, Su; Liu, Shanshan; Duan, Lijuan; Fan, Chaofeng; Jiang, Yan (Frontiers in Neurology, 2025)
ObjectiveThe aim of this study was to design a national and culturally appropriate questionnaire to assess the nurses’ knowledge, attitude and practice (KAP) for discharge planning of stroke patients and to test the reliability and validity of this questionnaire.MethodsThis questionnaire was developed using domestic and international literature and combining the KAP theory. It covered eight aspects of basic knowledge, relevant knowledge, psychological cognition, emotional tendency, intentional behavior, assessment, implementation and evaluation of discharge planning for stroke patients. The item pool was established through Delphi expert inquiry to form a pre-survey questionnaire. The pre-survey was first administered to 60 clinical nurses, then tested on 626 clinical nurses. Finally the questionnaire’s reliability was assessed through retest reliability, split-half reliability, and Cronbach’s α coefficient, while the validity of the scale was evaluated through content validity, structural validity, and factor analysis.ResultsThe final formal questionnaire was used to assess nurses’ KAP for discharge planning of stroke patients. The questionnaire consisted of 37 items in three dimensions: knowledge (12 items), attitude (10 items) and practice (15 items). The questionnaire had an average expert authority coefficient of 0.88, a consistency coefficient of 0.454, a total internal consistency reliability (Cronbach’s alpha coefficient) of 0.909, a retest reliability of 0.924, and a content validity index of 0.972. The results of this study were calculated on a dimensional basis, resulting in the following standard scores: 84.01 (<85) for the knowledge dimension, 90.61 (>85) for the attitude dimension, and 81.83 (<85) for the practice dimension. The correlation coefficients between the three dimensions and the total questionnaire were 0.635, 0.659, and 0.566, respectively. The Kaiser-Meyer-Olkin (KMO) value was 0.966, and the sphere test value was p < 0.0001.ConclusionThe questionnaire on nurses’ KAP for discharge planning of stroke patients showed good reliability and validity. It is suitable for use by clinical nurses. Nurses in Level-3 hospitals across the country need to improve their knowledge, attitude and practice regarding discharge planning for stroke patients.